SIRT1 Allele Frequencies in Depressed Patients of European Descent in Russia - Aftanas, Lyubomir I.; Anisimenko, Maksim S.; Berdyugina, Darya A.; Garanin, Aleksandr Yu.; Maximov, Vladimir N.; Voevoda, Mikhail I.; Vyalova, Natalya M.; Bokhan, Nikolay A.; Ivanova, Svetlana A.; Danilenko, Konstantin V.; Kovalenko, Sergei P. (Frontiers in Genetics, 2019)
Depressive disorder (DD) is a widespread mental disorder. Although DD is to some extent inherited, the genes contributing to the risk of this disorder and its genetic mechanisms remain poorly understood. A recent large-scale genome-wide association Chinese study revealed a strong association between the SIRT1 gene variants and DD. The aim of this study was to analyze the occurrence of heterozygote carriers and search for rare SNP variants of the SIRT1 gene in a cohort of DD patients as compared with a cohort of randomly selected members of the Russian population. The complete coding sequences of the SIRT1 gene from 1024 DNA samples from the general Russian population and from 244 samples from patients with DD were analyzed using targeted sequencing. Four new genetic variants of the SIRT1 were discovered. While no significant differences in the allele frequencies were found between the DD patients and the general population, differences between the frequencies of homozygote carriers of specific alleles and occurrences of heterozygous were found to be significant for rs2236318 (P<0.0001), and, putatively, rs7896005 (P<0.05), and rs36107781 (P<0.05). The study found for the first time that two new SNPs (i.e., 10:69665829 and 10:69665971) along with recently reported ones (rs773025707 and rs34701705), are putatively associated with DD. The revealed DD-associated SIRT1 SNPs might confer susceptibility to this disorder in Russian population of European descent.